VALIDITY OF GENETICS MATERIAL TOPIC STUDENT WORKSHEET BASED ON KNOW-WANT-LEARNED (KWL) STRATEGY TO TRAIN STUDENT METACOGNITIVE SKILLS - Nurul Ahillah; Endang Susantini (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
Gedung C3 Lt 2, Jalan Ketintang, Surabaya 60231, IndonesiaEmail: endangsusantini@unesa.ac.idAbstractThis research was aimed to produce valid student worksheet based on KWL (Know-Want-Learned) strategy for genetics material topic to train student metacognitive skills. The development was refferred to ADDIE model, consisted of Analyze, Design, Develop, Implement, and Evaluate phase. The research stage was begun by curriculum, concept, task, and student analysis then continued with design and development stage in Biology Department, Mathematics and Natural Sciences Faculty, Universitas Negeri Surabaya. The developed student worksheet was then implemented limitedly to fiften 12th grade students of SMA Negeri 1 Gresik. The observed parameters were the validity of the stundent worksheet and pretest-posttest questions. The data of worksheet and pretest-posttest questions validity obtained from the validation of an education expert, as well as the validation of a material genetics expert and a biology teacher that were analyzed based on mode. The validation result showed that the student worksheet and pretest-posttest questions were very valid with score 4 and 100%, respectively. Based on these results, it can be concluded that the student worksheet and pretest-posttest questions were very valid and worthy to be used in training student metacognitive skills.Keyword: student worksheet, KWL, metacognitive skills, genetics material